PENGARUH KEMANFAATAN NPWP, KUALITAS PELAYANAN DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (STUDI PADA KANTOR PELAYANAN PAJAK PRATAMA PEKANBARU SENAPELAN) - Rahmawati, Sri; -, Andreas; Ilham, Elfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The number of tax payers is increase for years. But, it is not balanced with the level of tax compliance. The compliance problem becomes an obstacle in optimizing the tax revenue. In KPP Pratama Pekanbaru Senapelan, the level of tax compliance is still low. It can be seen from comparison between the number of registered taxpayers with the number of taxpayers who report tax return. This research aimed to analyze the effect of the benefits of TIN, quality of services, and Taxpayer awareness on tax compliance. Data collection method used is a survey method using questionnaires media. The method of sampling was done by convenience sampling. The number of questionnaires that can be analyzed is 100 questionnariesfrom 100 correspondences who are as taxpayers listed in KPP Pratama Pekanbaru Senapelan. Data analysis techniques used in this research is linear regression analysis with SPSS version 20.0.The results of this research showed that the benefits of TIN had no effect on the tax compliance. Quality of services and taxpayer awareness had effect on the tax compliance.Keywords: Benefits of TIN, Quality of Service, Taxpayer Awareness, and Taxpayer Compliance